Recoil Proton Telescopes and Parallel Plate Avalanche Counters for the 235U(n, f) cross section measurement relative to H(n, n)H between 10 and 450 MeV neutron energy. (1st April 2023) - Manna, A.; Pirovano, E.; Aberle, O.; Amaducci, S.; Barbagallo, M.; Castelluccio, D.M.; Colonna, N.; Console Camprini, P.; Cosentino, L.; Dietz, M.; Ducasse, Q.; Finocchiaro, P.; et al.
Abstract: With the aim of measuring the 235 U(n, f) cross section at the n_TOF facility at CERN over a wide neutron energy range, a detection system consisting of two fission detectors and three detectors for neutron flux determination was realized. The neutron flux detectors are Recoil Proton Telescopes (RPTs), based on scintillators and solid state detectors, conceived to detect recoil protons from the neutron-proton elastic scattering reaction. This system, along with a fission chamber and an array of parallel plate avalanche counters for fission event detection, was installed for the measurement at the n_TOF facility in 2018, at CERN. An overview of the performances of two RPTs — especially developed for this measurement — and of the parallel plate avalanche counters are described in this article. In particular, the characterization in terms of detection efficiency by Monte Carlo simulations and response to neutron beam, the study of the background, dead time correction and characterization of the samples, are reported. The results of the present investigation show that the performances of these detectors are suitable for accurate measurements of fission reaction cross sections in the range from 10 to 450 MeV.